In Vitro evaluation of Licorice Root Ethanolic Extract Antibacterial Activity on Fusobacterium nucleatum in comparison to Chlorhexidine and Doxycycline - Mohammadreza Tabatabaeian; Vahid Esfahanian*; Arezoo Tahmourespour (Lorestan University of Medical Sciences, 2023)
Background and Aim: Antibiotics and mouthwashes which are used to prevent and treat periodontal diseases have side effects such as antibiotic resistance, mouth burning, and xerostomia. With the advancement of technology, plants have been considered as alternative antibacterial agents. Licorice plant with different species has been used in traditional medicine to treat gastritis and respiratory diseases. Considering the properties of licorice in traditional medicine, this study aimed to investigate the antibacterial properties of licorice root extract with different concentrations compared with Chlorhexidine mouthwash and Doxycycline antibiotic on Fusobacterium nucleatum in vitro. Materials & Methods: After the preparation of 0.5 McFarland bacterial suspension, the plant and its ethanolic extract, and six extract dilutions were also prepared. Agar disk diffusion and broth microdilution tests were carried out against Fusobacterium nucleatum ATCC 2558. The antibacterial effect of Chlorhexidine mouthwash 0.2% and Doxycycline 100 mg antibiotic were also determined to be compared with licorice extract. The data were analyzed using Mann-Whitney and Kruskal-Wallis statistical tests in spss26 software at a significance level of 5%. Results: All the six concentrations had significant antibacterial effects compared with each other, chlorhexidine and doxycycline (P-value<0.05). The inhibitory concentrations of extract, MIC50, MIC70, and, MIC90 were related to 12/5, 50, and 200 mg/ml, respectively. The inhibitory percentages of chlorhexidine and doxycycline were 67.6% and 88.7%, respectively. Conclusion: Licorice ethanolic extract exhibited an excellent antimicrobial effect (MIC=6.25mg/ml), so that in concentrations higher than 25, a greater antimicrobial effect was observed than in chlorhexidine (P<0.05).